A case report of thoracic endometriosis – A rare cause of haemothorax. (2017) - Pankratjevaite, Lina; Samiatina-Morkuniene, Diana
Highlights: The diagnosis of thoracic endometriosis is complicated, because it has no specific symptoms and signs, and often delayed. TES should be suspected in a reproductive age woman with exacerbating symptoms during the menstruation. TES treatment should be started with medicine. If medical therapy fails, surgical treatment should be performed. Our case report shows that TES may be the cause of dangerous situation when an urgent operation must be performed. It is the first case of TES that has required urgent surgical treatment in our hospital in past fifteen years. Not all clinicians know that TES sometimes might complicate to pneumothorax or massive bleeding, which might cost a patient's life. We suggest performing VATS as soon as possible for reproductive age woman with unknown aetiology of pneumothorax or haemothorax to find out the lesions in pleural cavity and start appropriate treatment on time. Abstract: Introduction: The presence of endometrial tissue in airways, pleura and lung parenchyma is called thoracic endometriosis syndrome (TES). It is a rare pathology, and typically consists of catamenial pneumothorax, haemothorax, haemoptysis, and pulmonary nodules. We report a case of a 36-year-old woman with thoracic endometriosis causing catamenial haemothorax. Conclusions: The diagnosis of thoracic endometriosis is complicated and often delayed. TES should be suspected in a reproductive age woman with exacerbating symptoms during the menstruation. Treatment may be medical and surgical.